PENGARUH PERMAINAN TRADISIONAL DAKON DENGAN MEDIA ALAM TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 4-5 TAHUN DI KB LATIVIYAH - Suhairiyah; Ianatuz Zahro; Trio Suwargono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the impact of the dakon game using natural media on the social and emotional development of early childhood children at KB Lativiyah. The background of this study is the emergence of social and emotional problems in children, such as difficulty in collaboration, lack of self-confidence, irritability, and reluctance to interact with peers. The dakon game, as a traditional game, was chosen because it contains educational values that can stimulate social skills and manage children's emotions in a natural and fun way. This study adopted a quantitative approach with an experimental design of one group pretest-posttest design. The study population consisted of 25 male and female students at KB Lativiyah, with a purposive sampling technique of 12 children taken. Dana P. Turner (2020) stated that purposive sampling is used when researchers want to focus on individuals who have certain characteristics relevant to the research interest. Data collection was carried out by observing social and emotional development compiled based on the STTPA indicators in Permendikbudristek No. 17 of 2023. Data analysis was conducted using descriptive statistics and hypothesis testing using the Wilcoxon test due to the ordinal scale of the data. In this way, the dakon game using natural media can be a good alternative learning strategy to stimulate the social and emotional development of early childhood. This study recommends that early childhood education teachers more routinely use traditional games as elements of relevant and meaningful learning. This study produced outputs in the form of increased understanding and concrete evidence regarding the effectiveness of the traditional dakon game made from natural materials as a means to stimulate the social and emotional development of early childhood. Using quantitative methods and a pretest-posttest design, this study revealed that the dakon game can improve several important aspects of children's social and emotional development, such as collaboration, sharing, waiting for turns, and recognizing and managing emotions in a positive way. The dakon game, which utilizes natural materials such as wood and seeds, also provides educational value and fosters a love of the environment. In addition, the practical results of this study are a guide to implementing the dakon game in early childhood education environments, which can be used by teachers as a thematic learning option rooted in local culture. The results of this study are expected to be used by early childhood education institutions to design contextual learning models that are fun, affordable, and support the achievement of development according to the STTPA (Standard Level of Child Development Achievement) indicators.